Implementasi Standar K3 (Keselamatan dan Kesehatan Kerja) Dalam Rangka Perlindungan Pekerja Di Industri Konstruksi - Alega; Muhammad Rizki Meidianto; Novelia Magdalena Pasaribu; Zakiya Az Zikra Ismail (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Occupational Safety and Health (K3) is vital in the construction industry, which faces high risks of work accidents. Implementing K3 standards is not only a legal requirement but also a strategic effort to protect workers and boost productivity. Workers have the right to protection under regulations, including the 1945 Constitution of Indonesia and Law No. 13 of 2003 on Employment. This article examines the company's responsibilities in ensuring safety, such as providing personal protective equipment (PPE) and regular safety training. Using a qualitative approach, the study explores existing regulations, challenges in K3 implementation, and solutions to create a safe work environment. Findings emphasize the importance of K3 education and training in fostering a safety culture. By taking these steps, companies fulfill legal duties while demonstrating commitment to safeguarding human resources as essential assets for sustainable business operations.